Can the fear recognition deficits associated with callous-unemotional traits be identified in early childhood?. Issue 6 (2nd July 2016) - White, Stuart F.; Briggs-Gowan, Margaret J.; Voss, Joel L.; Petitclerc, Amelie; McCarthy, Kimberly; R. Blair, R. James; Wakschlag, Lauren S.
ABSTRACT: Introduction : Callous-unemotional (CU) traits in the presence of conduct problems are associated with increased risk of severe antisocial behavior. Developmentally sensitive methods of assessing CU traits have recently been generated, but their construct validity in relation to neurocognitive underpinnings of CU has not been demonstrated. The current study sought to investigate whether the fear-specific emotion recognition deficits associated with CU traits in older individuals are developmentally expressed in young children as low concern for others and punishment insensitivity. Method : A subsample of 337 preschoolers (mean age 4.8 years, SD = 0.8) who completed neurocognitive tasks was taken from a larger project of preschool psychopathology. Children completed an emotional recognition task in which they were asked to identify the emotional face from the neutral faces in an array. CU traits were assessed using the Low Concern (LC) and Punishment Insensitivity (PI) subscales of the Multidimensional Assessment Profile of Disruptive Behavior (MAP-DB), which were specifically designed to differentiate the normative misbehavior of early childhood from atypical patterns. Results : High LC, but not PI, scores were associated with a fear-specific deficit in emotion recognition. Girls were more accurate than boys in identifying emotional expressions but no significant interaction between LC or PI and sex was observed. Conclusions : Fear recognition deficits associated with CU traits in older individuals were observed in preschoolers with developmentally defined patterns of low concern for others. Confirming that the link between CU-related impairments in empathy and distinct neurocognitive deficits is present in very young children suggests that developmentally specified measurement can detect the substrates of these severe behavioral patterns beginning much earlier than prior work. Exploring the development of CU traits and disruptive behavior disorders at very early ages may provide insights critical to early intervention and prevention of severe antisocial behavior.